Consumer behaviour and financing pattern of Malaysia through the economic cycles: 1997 to 2005 - Lee, Jade Lee Yoke (Universiti Utara Malaysia, 2009)
This study will help to shed light on consumer spending and financing in Malaysia.The descriptive and quantitative analyses focuses on how Malaysian consumer spending and financing patterns may change through the economic cycles from 1997 to 2005 and establishes the relationships that will be helpful in predicting the result of the financial and economic shocks. The patterns of residential property loans and various types of consumer credit were examined in relation to the performance of the economy as measured by real GDP. Observations were also made on the trend of purchases on credit basis.The finding shows that there is direct correlation and positive growth for consumer credits throughout the economic cycles. However for residential property it is inversely correlated.In both categories, during an economic downturn there will be contractions in the outstanding loans but it is still viable to extend credit to selected portfolio.